(untitled) (Baghdad Science Journal, 2012)
Three groups of subjects have been divided (25/group): healthy normotensive non-pregnant women (Group A), normal normotensive pregnant women (Group B), and women with preeclampsia (Group C).The levels of serum alanine aminotransferase (ALT), aspartate aminotransferase (AST), total bilirubin , creatinine , blood urea nitrogen, triglyceride , total cholesterol and glucose have been estimated in all subjects. All measured parameters were determined by spectrophotometric analysis. The results showed a significant(P